A bibliometric analysis of green manufacturing and similar frameworks. Issue 4 (8th June 2015) - Sangwan, Kuldip Singh; Mittal, Varinder Kumar
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to review the green manufacturing and similar frameworks in order to trace the origin, definitions, scope, similarities, differences, and publications of these manufacturing frameworks. Design/methodology/approach – A review of 113 research articles is conducted for various terms, namely, green manufacturing (GM); environmentally conscious manufacturing; environmentally responsible manufacturing; environmentally benign manufacturing; sustainable manufacturing; clean manufacturing; cleaner production; sustainable production with reference to triple bottom line, product life cycle engineering, systems approach, resource and energy efficiency, supply chain, pollution prevention and closed loop system/6R. Findings – It can be said with reasonable confidence that all these eight frameworks have been used interchangeably by researchers but it requires some standardization. It has been observed during literature review that to standardize the terminology researchers have to clear emphatically in their research the use of various life cycle engineering approach; clarity on the end-of-life strategies used; clarity in use of various components of triple bottom line perspectives; inclusion of the whole supply chain and integration of environmental improvement strategies with the business strategy. Research limitations/implications – The literature reviewed for the study is the literature available online using Google scholar. Originality/value – This is one of the first known studies to review the GM and similar frameworks for their origin, definition, scope, similarities, and differences.